Bi treatment with hydralazine/nitrates vs. placebo in Africans admitted with acute HEart Failure (BA‐HEF). (20th May 2016) - Sliwa, Karen; Damasceno, Albertino; Davison, Beth A.; Mayosi, Bongani M.; Sani, Mahmoud U.; Ogah, Okekuchwu; Mondo, Charles; Ojji, Dike; Dzudie, Anastase; Kouam, Charles Kouam; Yonga, Gerald; Ba, Serigne Abdou; et al.
Abstract: Aims: Patients with acute heart failure (HF) in Africa are rarely being treated with a hydralazine/nitrates combination. Therefore the effect of this treatment was studied here. Methods and results: The study was planned to enrol 500 patients during an acute HF admission, from nine sub‐Saharan African countries. Patients were randomized in a double‐blind manner to receive 50 mg hydralazine/20 mg isosorbide dinitrate (HYIS) t.i.d. or matching placebo for 24 weeks followed by open label HYIS for all patients. The study was terminated after 147 patients were enrolled due mostly to issues with recruitment into a prospective, placebo‐controlled study. Most patients were recruited from Mozambique, South Africa, Kenya, and Uganda. The primary endpoint of death or HF readmission through 24 weeks was neutral [hazard ratio (HR) 1.05, 95% confidence interval (CI) 0.48–2.27, P = 0.90] in the 133 randomized patients included in the analyses. There were non‐signficant effects in favour of HYIS in secondary endpoints including change in dyspnoea severity at day 7 or discharge, decrease in systolic blood pressure, greater decrease in weight, and increase in 6‐min walk test distance at week 24. There were also small changes in echocardiographic indices of cardiac size and function in favour or HYIS, but none was significant. Conclusion: The BA‐HEF trial demonstrated challenges in recruiting the expected number of patients with acute HF in a number of African countries, which highlights the need for strategic logistic support. Trial registration : NCT01822808.